Inflammatory bowel disease and rheumatoid arthritis - Zong-Biao TAN; Chuan LIU; Su-Qi ZENG; Wei-Guo DONG (Yixue xinzhi zazhi, 2022)
The incidence of inflammatory bowel disease and rheumatoid arthritis have been in-creasing in recent years. These are both autoimmune diseases with similar pathogenesis involving com-plex interactions between immunity, inflammation, the intestinal microbiome and genetics. Epidemio-logical evidence suggests an increased risk of rheumatoid arthritis in patients with inflammatory bowel disease, which is often difficult to distinguish in the early stages of the disease because of the presence of arthritis symptoms in both cases. In terms of treatment, there are also drugs that cover both diseases. This article reviews the relationship between inflammatory bowel disease and rheumatoid arthritis in order to provide a basis for early identification and timely treatment of both.